Three-Dimensional Morphometry of Single Endothelial Cells with Substrate Stretching and Image-Based Finite Element Modeling. (14th July 2009) - Yamada Yamada, Hiroshi Hiroshi; Mouri Mouri, Norihide Norihide; Nobuhara Nobuhara, Shinji Shinji
Abstract : Morphologically accurate reproduction of the behavior of endothelial cells is a key to understanding their mechanical behavior in cyclically inflated arteries and to quantitatively correlating this with cellular responses. We developed a novel technique to measure the three-dimensional geometry of cells on the substrate being stretched. We obtained sliced images of cells using confocal laser-scanning microscopy, and created image-based finite element models in the unloaded state assuming neo-Hookean material. Comparison of numerical predictions and experiments involving six cells when the substrate was stretched by 15% showed that the deformed geometry agreed with an average error of < 0.55 μ m, roughly one-hundredth the size of a cell, for the lower half of the range of cellular height. Numerical sensitivity analyses showed that the cellular deformation under substrate stretching, that is, displacement boundaries, is insensitive to the absolute value of the elastic modulus, but depends on the nuclear to cytoplasmic modulus ratio.